1998
DOI: 10.1021/jo981740h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chlorosilyl Enolates

Abstract: A variety of chlorosilyl enolates has been prepared starting from esters, thiol esters, acylsilanes, and ketones. Two general methods are involved, direct enolsilylation with trichlorosilyl triflate and diisopropylethylamine, and a number of methods based on electrophilic substitution of either C-or O-silyl or stannyl carbonyl compounds. The most useful method is a Hg(OAc) 2 -catalyzed transsilylation from trimethylsilyl to trichlorosilyl enol ethers, providing a wide range of ketone enolates in good to high y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…Conversions of 9a/b in the presence of LiCl or LiI and TMSCl afforded some type 8/10/12 indolizidinones, but the isolated yields were low. [27] Obviously, the removal of the benzyl group by von Braun-type degradation of an intermediate acyl ammonium salt was the crucial step. [28] The competing lactonization (Ǟ 11) was the major reaction path, especially when handling more than 1 mmol quantities of the epoxides 9a/b.…”
Section: Resultsmentioning
confidence: 99%
“…Conversions of 9a/b in the presence of LiCl or LiI and TMSCl afforded some type 8/10/12 indolizidinones, but the isolated yields were low. [27] Obviously, the removal of the benzyl group by von Braun-type degradation of an intermediate acyl ammonium salt was the crucial step. [28] The competing lactonization (Ǟ 11) was the major reaction path, especially when handling more than 1 mmol quantities of the epoxides 9a/b.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in this laboratory have shown that enol silylation of ketones with SiCl 4 and an amine base is catalyzed by hexamethylphosphoric triamide (HMPA) (43). We were pleased to find that the reaction of isobutyraldehyde with SiCl 4 and triethylamine in the presence of 10 mol % HMPA in methylene chloride proceeded smoothly at room temperature to afford trichlorosilyl enolate 2 (Fig.…”
Section: Preparation Of Trichlorosilyl Enolatementioning
confidence: 94%
“…The synthesis of trichlorosilyl enolates derived from ketones was previously accomplished by metathesis of trimethylsilyl enol ethers with silicon tetrachloride (SiCl 4 ) in the presence of a catalytic amount of mercury(II) acetate or palladium(II) acetate (43). In the presence of 5 mol % of either Hg(OAc) 2 or Pd(OAc) 2 , the metathetical reaction of trimethyl-[2-methyl-(propenyloxy)]silane 1 with SiCl 4 proceeded very slowly at room temperature to afford only trace amounts of trichlorosilyl enolate 2 according to 1 H NMR analysis (Fig.…”
Section: Preparation Of Trichlorosilyl Enolatementioning
confidence: 99%
“…Recently, Denmark et al [5] examined the effectiveness of chiral derivatives of HMPA as Lewis base promoters 2 ) 3 ) in several enantioselective reactions, including the so-called desymmetrization of meso-epoxides and aldol additions (Scheme 1, Eqns. 1 and 2).…”
mentioning
confidence: 99%
“…4 ) For recent reviews on applications of 1-phenylethylamine in the preparation of enantiomerically pure compounds, see [8]. 5 ) For N-monoalkylations of 1-phenylethylamine in DMPU solution, see [9]. 6 ) The moderate yield encountered in the cyclization reaction is a consequence of oligomer formation [12].…”
mentioning
confidence: 99%